PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, FASILITAS PEMBELAJARAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU MATEMATIKA DI POKJA 3 KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The aims of this research are to find out the influence of : (1) Principals’ Leadership Style, Infrastuctures, and Work Motivation on teachers’ performance together. (2) Principals’ Leadership Style on teachers’ performance partialy. (3) Infrastuctures on teachers’ performance partialy (4) Work Motivation on teachers’ performance partialy in Junior High School of Pokja 3 Wonosobo Regency.This research was a survey research using quantitative correlation research approach. This research was done in 19 Junior High Schools of Pokja 3 Wonosobo Regency. The population of the research was mathematic teachers in Junior High Schools of Pokja 3 Wonosobo Regency, they were 41 people. All of them as sample of the research. The data were collected using questionnaire and analyzed by multiple regressions and continued by partial correlation analysis by using SPSS computer program.The results of this research show that (a) there is positive and significant influence of principals’ leadership style, infrastructures and work motivation on the teachers’ performance of  mathematic teachers in Junior  High Schools. (b) there is positive and significant influence of principals’ leadership style on mathematic teachers’ performance (c) there is positive and significant influence of infrastructures on mathematic teachers’ performance. (d) there is positive and significant influence of work motivation on mathematic teachers’ performance. The result of this research shows that the better The principals’ leadership style, Infrastuctures, and Work motivation, the better mathematic teachers’ performance in Junior High School of Pokja 3 Wonosobo Regency. Therefore the more empower The principals’ leadership style, Infrastructures, and Work motivation together to the positive direction so it can be predicted it willl give positive contribution to the teachers’ performance.